Cancer and Tumour Suppressor p53 Encounters at the Juncture of Sex Disparity - Haupt, Sue; Haupt, Ygal (Frontiers in Genetics, 2021)
There are many differences in cancer manifestation between men and women. New understanding of the origin of these point to fundamental distinctions in the genetic code and its demise. Tumour suppressor protein p53 is the chief operating officer of cancer defence and critically acts to safeguard against sustained DNA damaged. p53 cannot be ignored in cancer sex disparity. In this review we discuss the greater prevalence and associated death rates for non-reproductive cancers in men. The major tumour suppressor protein p53, encoded in the TP53 gene is our chosen context. It is fitting to ask why TP53 mutation incidence is estimated to be disproportionately higher among males in the population for these types of cancers compared with females? We scrutinise the literature for evidence of predisposing genetic and epigenetic alterations that may explain this sex bias. Our second approach is to explore whether redox activity, either externally imposed or inherent to males and females, may define distinct risks that could explain the clear cancer sex disparities.